(untitled) (Studia theodisca, 2019)
In Vladimir Vertlib’s novel Viktor hilft reinventing identity, linguistic and cultural hybridization processes as well as re-localizations can be explained. The author describes polyphonic situations in the cross-cultural narrative process and indirectly pluralizes the concept of culture, advocating a transcultural understanding of modern cultures. The identity of literary figures, which require the foil of otherness, constructs itself in an overarching field of cultures. The discourse about the other shapes their own self-image.